MLA's professional development program: how we took control of our future. - Roper, F W (1998)
This article, which focuses primarily on the last fifty years, reviews the evolution and expansion of MLA's professional development activities. It shows how an integrated professional development program has emerged from a group of individual activities with little coordination among them. Continuing review, discussion, and new initiatives are needed to ensure that the membership is equipped with the knowledge and skills needed to function effectively in the twenty-first century.